PENERAPAN MODEL PEMBELAJRAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK, IPAS TENTANG SIFAT-SIFAT BUNYI KELAS IV SD NEGERI BATUPLAT 1 - Koro, Maxsel; Nawa, Netty Elisabeth Antoneta; Dafa, Alfarado Desandro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The formulation of the research problem is: how to apply the inquiry learning model to improve the learning outcomes of science on the material of sound properties in grade IV SD Negeri Batuplat 1. The purpose of this study is to determine how to apply the inquiry learning model to improve student learning outcomes on the material of sound properties in grade IV SD Negeri Batuplat. This type of research is classroom action research (PTK) which is conducted through a collaborative process between researchers and class teachers and the research subjects are 26 students from grade IV of Batuplat 1 elementary school consisting of 19 males and 7 females. This research was conducted in two cycles, the method used in this research is a qualitative descriptive method. Data collection techniques used in this research are observation, interviews, posttests and pretests, and documentation. The results of this study indicate that there is progress in student learning outcomes using the inquiry learning model, this is evidenced by the achievement of the average student score increasing to 92.64%. the results of this increase can be seem from the posttest and pretest scores as well as the observation scores given. Based on the research results above, it is concluded that the application of learning using the inquiry learning model to improve the learning outcomes of grade IV students of Batuplat q elementary school kupang city is very beneficial.